Long term impacts of early social environment on chimpanzee white matter - Michele M. Mulholland; Erin Hecht; Michael J. Wesley; William D. Hopkins (Scientific Reports)
Abstract Early adverse rearing conditions are known to have deleterious consequences on social behavior, cognition, and brain development of both human and nonhuman primates. We analyzed archival diffusion tensor imaging (DTI) data from mother- (MR) or nursery-reared (NR) chimpanzees and used support vector machine learning to determine whether we could retrospectively classify chimpanzees as MR or NR based on white matter fractional anisotropy (FA) decades after their rearing experiences. A significant proportion of chimpanzees were correctly classified as MR and NR based on white matter fractional anisotropy (76.32%; p = 0.004). Voxel-based morphometry revealed that MR chimpanzees had increased FA in the splenium/isthmus of the corpus collosum and premotor cortex, while NR chimpanzees had increased FA in the thalamic region, cuneus, and lateral genu of the corpus collosum (p < 0.01). A subset of the NR chimpanzees participated in early social interventions, but unlike gray matter, these interventions do not explain misclassification based on white matter. These findings suggest that nursery rearing has long-term effects on both gray and white matter, but that early interventions may ameliorate the effects on gray matter only. Future research should investigate the effectiveness and relative contributions of combined social, cognitive, and nutritional interventions on brain development in nonhuman primates.